DYE YIELDING PLANT DIVERSITY OF DISTRICT RAJOURI, JAMMU AND KASHMIR STATE-INDIA - ABDUL RASHID, (International Journal of Pharma and Bio Sciences, 2013)
District Rajouri laying at 300 – 50/ N to 330 – 30/ N longitude and 740 E to 740 – 10/ E latitude, with diverse climatic conditions and varying altitudinal zones (490-4700 m.) exhibit a great degree of plant diversity. Survey of the literature revealed that many authors have contributed to ethnobotany and plant diversity studies of the Jammu and Kashmir state but the enlisting of dye yielding plant diversity has not been done so far. Therefore the purpose of the present study was to document the dye yielding plant diversity and associated knowledge from the study area. Forty-eight dyes yielding plant species belonging to twenty-seven families were reported from the study area. The botanical identity of the reported plant species with family, local name, habit and part used has been documented in present work. The study revealed that a considerable plant resource base for natural dyes exists in the study area but remained in the wild and unutilised for this purpose. The present work has opened up a new window for the future studies on the various aspects of the reported taxa including extensive exploration for updating of the present list and to study the conservational aspects of the disappearing flora of the region.